The effects of intermittent sprint training on running economy and leg stiffness in highly trained runners - Thibault, D.; Ellis, C.; Toms, G. B.; Schaefer, A.; Titcomb, D. (International Journal of Exercise Science, 2025)
The purpose of this study was to evaluate the impact of once-weekly sprint training on running economy (RE) and leg stiffness (LS) in highly trained athletes (12 M, 13 F, mean age 24.8 ± 7.1). Participants were recruited based on weekly exercise volume (minimum 4 hours) and athletic ability calculated by World Athletics score (minimum 500). RE and LS were evaluated at three velocities before and after 12 weeks of once-weekly sprint training. On average, participants experienced a non-statistically significant improvement in RE (average percent change -2.0 ± 5.6%, -1.2 ± 5.2%, -1.0 ± 4.6%, p = 0.389, 0.269, 0.272, Cohen`s d = 0.21, 0.18, 0.17), and a statistically significant improvement in LS (12.59 ± 9.2%, 11.49 ± 10.9%, 15.67 ± 11.2%, p = 0.019, 0.027, 0.011, Cohen`s d = 0.61, 0.56, 0.68) at the three running velocities. Interestingly, the improvement in LS was significantly influenced by a reduction in vertical displacement during the gait cycle (-17.7 ± 11.7%, -15.7 ± 12.2, -17.3 ± 13.4%, p < 0.001, = 0.001, = 0.001, Cohen`s d = 1.10, 0.93, 0.91). Changes in RE and LS were significantly different when data were analyzed by exercise volume during the intervention period (p < 0.05). The present study demonstrates that LS, independently shown to improve performance and RE, can be improved by sprint training in highly trained athletes. Additionally, the average participant improvement in RE suggests that sprint training may lead to statistically significant improvement with an increase in participants and tighter participant training control.